2012
DOI: 10.1016/j.jvs.2012.04.049
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of Diet in Renal Disease 4-calculated glomerular filtration rate is a better prognostic factor of cardiovascular events than classical cardiovascular risk factors in patients with peripheral arterial disease

Abstract: The MDRD-4 GFR was a better predictor of risk of death or infarction than classical cardiovascular risk factors in patients with PAD. This suggests that its routine use in the initial evaluation in patients with PAD is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…11 Kidney function has increasingly displayed greater predictive value of CV events in patients with atherosclerosis than traditional risk factors. 9,10 Kidney failure patients have extremely low FMD, even more so than those of PAD patients. 29 Once advanced kidney disease is present, it may contribute to the progression of systemic endothelial dysfunction more than traditional cardiovascular risk factors do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Kidney function has increasingly displayed greater predictive value of CV events in patients with atherosclerosis than traditional risk factors. 9,10 Kidney failure patients have extremely low FMD, even more so than those of PAD patients. 29 Once advanced kidney disease is present, it may contribute to the progression of systemic endothelial dysfunction more than traditional cardiovascular risk factors do.…”
Section: Discussionmentioning
confidence: 99%
“…7 Current evidence suggests that decreased kidney function is not only an independent predictor of CV events, it may also be a stronger predictor than traditional risk factors. 9,10 In the setting of PAD, the presence of kidney disease predicts worse outcomes after peripheral revascularization. 11 Kidney disease is known to produce a state of oxidative stress and inflammation, 12 both of which are strong depressors of endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports provide evidence supporting the association between renal function and atherosclerosis, and eGFR is an independent prognostic factor for cardiovascular disease [32]. We recently reported that eGFR is an excellent predictor of vascular events in patients with peripheral arterial disease [33]. Since RI could indicate the atherosclerosis level of patients, our results suggest that the effect of smoking on local levels of mPGES-1/EP-4 is independent of the atherosclerosis and COPD states of patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…GFR was estimated from standardized serum creatinine using the 4-variable Modification of Diet in Renal Disease (MDRD) equation. Serum creatinine was measured using the Jaffe alkaline picrate method (Hoffmann-La Roche, USA) traceable to isotope dilution mass spectrometry values [15].…”
Section: Methodsmentioning
confidence: 99%